Pengaruh Pengelolaan Keuangan Desa Terhadap Pembangunan Infrastruktur di Desa Wonggarasi Barat Kec. Lemito Kab. Pohuwato - Zainun Botutihe; Fahrudin Zain Olilingo; Mentari Rizki Sawitri Pilomonu (Masyarakat Ekonomi Syariah Bogor, 2024)
Village financial management is an activity that includes planning. implementation, administration, reporting, and financial accountability, which is conducted through transparency, accountability, participation, systematic, and discipline. This study aimed to determine the influence of village financial management on infrastructure development in Wonggarasi Barat Village, Lemito Sub-District, Pohuwato Regency. This study used a descriptive quantitative method obtained from distributing questionnaires to the community in Wonggarasi Barat Village, Lemito Sub-District, Pohuwato Regency. The 80 samples in this study were determined through the Solvin formula with the purposive sampling technique. The analysis technique in this study used a statistical t-test and an adjusted R square test. The results disclosed that village financial management had a positive and significant effect on infrastructure development, although it had a low quality of human resources (HR) among the community and the village government. In addition, distrust towards the village government in managing funds from the central government somehow hindered the management, the community still considers that the government is not transparent in managing the village funds.